Description of a new species of Dascillus Latreille from Yunnan, China (Coleoptera: Dascillidae) - Li, Fengming; Ślipiński, Adam; Jin, Zhenyu (Zootaxa, 2017)
Dascillidae are a small and rarely studied family that includes nine currently recognized genera (Lawrence 2016; Ivie & Barclay 2011; Jin et al. 2013) and about 80 described species divided into two poorly defined subfamilies—Dascillinae and Karumiinae. In recent years, Jin et al. (2013, 2016, 2017) studied the species of Dascillinae and described 13 new species of Dascillus Latreille, 1797. At present, 33 species are included in this genus. Of these, 27 have been reported from China (Jin et al. 2016, 2017; Löbl & Löbl 2016; Terzani et al. 2017). Consequently, the Chinese fauna of Dascillus is extraordinarily rich.